IL-23 Contributes to Campylobacter jejuni-Induced Intestinal Pathology via Promoting IL-17 and IFNγ Responses by Innate Lymphoid Cells - Jing, Xi; Korchagina, Anna A.; Shein, Sergey A.; Muraoka, Wayne T.; Koroleva, Ekaterina; Tumanov, Alexei V. (Frontiers in Immunology, 2021)
Human pathogen Campylobacter jejuni is a significant risk factor for the development of long-term intestinal dysfunction although the cellular and molecular mechanisms remain scantily defined. IL-23 is an emerging therapeutic target for the treatment of inflammatory intestinal diseases, however its role in C. jejuni-driven intestinal pathology is not fully understood. IL-10 deficient mice represent a robust model to study the pathogenesis of C. jejuni infection because C. jejuni infection of mice lacking IL-10 results in symptoms and pathology that resemble human campylobacteriosis. To determine the role of IL-23 in C. jejuni-driven intestinal inflammation, we studied the disease pathogenesis in IL-23-/- mice with inhibited IL-10Rα signaling. These mice exhibited reduced intestinal pathology independent from bacterial clearance. Further, levels of IFNγ, IL-17, IL-22, TNF, and IL-6 were reduced and associated with reduced accumulation of neutrophils, eosinophils, monocytes and macrophages in the colon. Flow cytometry analysis revealed reduced production of IL-17 and IFNγ by group 1 and 3 innate lymphoid cells. Thus, our data suggest that IL-23 contributes to intestinal inflammation in C. jejuni infected mice by promoting IL-17 and IFNγ production by innate lymphoid cells.